2023
DOI: 10.3390/v15071594
|View full text |Cite
|
Sign up to set email alerts
|

First Insight into the Seroepidemiology of Hepatitis E Virus (HEV) in Dogs, Cats, Horses, Cattle, Sheep, and Goats from Bulgaria

Ilia Tsachev,
Krasimira Gospodinova,
Roman Pepovich
et al.

Abstract: In recent years, hepatitis E virus (HEV) infection has been found to be widespread among different animal species worldwide. In Bulgaria, high HEV seropositivity was found among pigs (60.3%), wild boars (40.8%), and East Balkan swine (82.5%). The aim of the present study was to establish the seroprevalence of HEV among dogs, cats, horses, cattle, sheep, and goats in Bulgaria. In total, 720 serum samples from six animal species were randomly collected: dogs—90 samples; cats—90; horses—180; cattle—180; sheep—90;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 79 publications
0
11
0
Order By: Relevance
“…A study performed in the Netherlands found HEV-specific antibodies in 18.52% of pet dogs but viral RNA was not detected in these animals [ 16 ]. Similarly, a seroprevalence of 21.1% was found in Bulgaria [ 17 ]. Even in Germany and Switzerland, where >50% and 38% of the animals showed antibodies against HEV, respectively, the virus was not detectable [ 18 , 19 ].…”
Section: Discussionmentioning
confidence: 98%
“…A study performed in the Netherlands found HEV-specific antibodies in 18.52% of pet dogs but viral RNA was not detected in these animals [ 16 ]. Similarly, a seroprevalence of 21.1% was found in Bulgaria [ 17 ]. Even in Germany and Switzerland, where >50% and 38% of the animals showed antibodies against HEV, respectively, the virus was not detectable [ 18 , 19 ].…”
Section: Discussionmentioning
confidence: 98%
“…The patient in the present study had consumed horse sashimi approximately 1 month prior to the onset of his symptoms, such as abdominal distention, loss of appetite, epigastric pain and dark urine (jaundice). It has been reported that anti-HEV IgG antibody and/or HEV RNA are positive in workhorses or horses in Egypt ( 28 ), China ( 29 ), the Netherlands ( 30 ), Bulgaria ( 31 ) and Germany ( 32 ). However, since whether horses play a role in the transmission of HEV remains unknown, further studies are warranted in this regard.…”
Section: Discussionmentioning
confidence: 99%
“…Seroprevalence in sheep varies from 0% to 24.4%. The highest seroprevalence was observed in Bulgaria (24.4%) [60]; followed by Italy (21.3%) [81] and (21.6%) [82]; Portugal (16.6%) [83]; and Spain (2.1%) [84] and (1.92%) [65]. In the Americas there has been only one study from Brazil, which showed 0% seropositivity [67].…”
Section: Seroprevalence Of Hepatitis E Virus In Ruminantsmentioning
confidence: 94%
“…Worldwide, the HEV seroprevalence in cows varies from 0.0% to 29.35%; in Europe, anti-HEV antibodies (Abs) were proven in only one study from Bulgaria (7.7%) [60], it was excluded in Spain (0.0%) [65]. In the Americas, data vary widely: the USA (20.4%) [66] and Brazil (1.42%) [67].…”
Section: Seroprevalence Of Hepatitis E Virus In Ruminantsmentioning
confidence: 99%
See 1 more Smart Citation